An analysis of the distribution characteristics of plantar pressure during running with different sports shoes - Li, J.; Liang, D. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Studies have previously shown that sports shoes can change the kinematic characteristics of the body. This change can directly impact on the distribution of plantar pressure. This research is intended to examine the effects of sports shoes on changes in plantar pressure distribution characteristics. The measures will compare the force under two different conditions.